1999
DOI: 10.1002/hep.510300504
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diagnosis of hepatitis C virus on quality of life

Abstract: Many patients with chronic hepatitis C virus (HCV) infection report disabling fatigue and a reduced sense of well-being. Scores on quality of life (QOL) scales, such as the Sickness Impact Profile or the Short Form 36 (SF-36) scale, have been reported as significantly worse for patients with HCV than for healthy controls. 1-3 These studies could not, however, determine the impact of HCV diagnosis per se on QOL because all patients were aware of their diagnosis at the time of completion of the QOL scales. A rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
213
3
5

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 276 publications
(231 citation statements)
references
References 9 publications
10
213
3
5
Order By: Relevance
“…Fatigue is generally the most frequently reported extrahepatic symptom in patients with CHC, although some researchers suggest that this fatigue is more closely related to depression severity than to hepatic disease itself. 6,8,15,33,35,36,49 Fatigue is reported to affect response to IFN-based therapy. 35 Maddock et al 64 used four self-report questionnaires to monitor side effects and HRQL in 29 patients with CHC and reported that patients experiencing severe fatigue were less likely to respond to therapy.…”
Section: Side Effects Of Chc Treatment and Their Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…Fatigue is generally the most frequently reported extrahepatic symptom in patients with CHC, although some researchers suggest that this fatigue is more closely related to depression severity than to hepatic disease itself. 6,8,15,33,35,36,49 Fatigue is reported to affect response to IFN-based therapy. 35 Maddock et al 64 used four self-report questionnaires to monitor side effects and HRQL in 29 patients with CHC and reported that patients experiencing severe fatigue were less likely to respond to therapy.…”
Section: Side Effects Of Chc Treatment and Their Managementmentioning
confidence: 99%
“…Fatigue was reported in 53% of patients and was disabling in 17%, 35 findings consistent with those of other studies in which the prevalence ranged from 50% to 67%. 6,8,15,33,35,36 Fatigue was also independently associated with age and female sex. Fatigue was not associated with viral factors.…”
mentioning
confidence: 95%
See 3 more Smart Citations